Design of a potent anticancer lead inspired by natural products from traditional Indian medicine. Issue 12 (12th August 2020) - Arya, Hemant; Yadav, C. Suresh; Lin, Shu-Yu; Syed, Safiulla Basha; Charles, Mariasoosai Ramya Chandar; Kannadasan, Sathananthan; Hsieh, Hsing-Pang; Singh, Sorokhaibam Sureshkumar; Gajurel, Padma Raj; Coumar, Mohane Selvaraj
Abstract: Among the plant constituents of Clerodendrum colebrookianum Walp., acteoside, martinoside, and osmanthuside β6 interact with ROCK, a drug target for cancer. In this study, aglycone fragments of these plant constituents (caffeic acid, ferulic acid, and p -coumaric acid) along with the homopiperazine ring of fasudil (standard ROCK inhibitor) were used to design hybrid molecules. The designed molecules interact with the key hinge region residue Met156/Met157 of ROCK I/II in a stable manner according to our docking and molecular dynamics simulations. These compounds were synthesized and tested in vitro in SW480, MDA-MB-231, and A-549 cancer cell lines. The most promising compound was chemically optimized to obtain a thiourea analog, 6a (IC50 = 25 µM), which has >3-fold higher antiproliferative activity than fasudil (IC50 = 87 µM) in SW480 cells. Treatment with this molecule also inhibits the migration of colon cancer cells and induces cell apoptosis. Further, SPR experiments suggests that the binding affinity of 6a with ROCK I protein is better than that of fasudil. Hence, the drug-like natural product analog 6a constitutes a highly promising new anticancer lead. Communicated by Ramaswamy H. Sarma